The global economic costs of the need to treat polluted water. Issue 3 (2nd July 2016) - Cazcarro, Ignacio; López-Morales, Carlos A.; Duchin, Faye
ABSTRACT: We estimate the global costs and other implications of the need to treat wastewater before it can be re-used. We extend the World Trade Model by creating water treatment sectors and provide alternative sources of water for satisfying users' quantity and quality requirements. The database distinguishes qualities and quantities of water endowments, sectoral water requirements, and wastewater discharges. We estimate that global water treatment costs could be reduced by several trillion dollars if water endowments were maintained at higher quality than currently is the case. Under scenarios where water quality degrades further, the treatment costs more than double even without taking account of likely increases in quality requirements. This modeling framework provides a starting point not only for more detailed empirical investigations of water management strategies, but also for examining prospects and associated costs for recovering other resources, such as metals, which can be reused multiple times.